Analysis of the impact of changes in tax legislation on tax revenues in the structure of the Iraqi tax system for the period 2004-2015 (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The tax system is no longer merely a mechanism for collecting public resource, but it has several dimensions, including economic, which is reflected in the fact that it is an important and effective tool in maintaining economic growth, fighting economicfluctuations, working towards achieving economic stability as well as social and political goals. It is a formulation of the of the principles and rules of tax policy in the form of laws, and these laws should be drafted in such a way as to ensure the achievement of their objectives. How tax laws should be flexible to adapt and the economic conditions of the state. Accordingly, the aim of the research was to analyze the effect of the changes in the tax legislation on the tax collection in the structure of the Iraq tax system for the period 2004- 2015, this study was divided into two sections. The first section included the concept and the most important changes in the tax legislation. In the tax legislation on the tax revenue in the structure of the Iraq tax system.